Anisotropic Thermal Characteristics of Graphene-Embedded Polyimide Composite Sheets. Issue 5 (June 2016) - Park, Seong-Yeob; Bae, Jong-Seong; Kim, Jin-Gyu; Oh, Min-Wook; Kim, Jungsoo; Nam, Dae-Geun; Yeum, Jeong Hyun; Oh, Weontae
Polyimide-graphene (PIG) composites were prepared, and their thermal properties were characterized as films or sheets. Graphene loadings were controlled up to 8 wt.% or 12 wt.% in their composites. The graphenes used in this work were prepared by the chemical treatment of graphite. The as-prepared polyimide-graphene composites were thermally characterized in films or sheets. The thermal conductivities of the PIG sheets were separately analyzed in both in-plane and out-of-plane directions. The thermal expansion coefficients (TECs) of the PIG composites slightly changed with the amount of graphene added to the composites. The in-plane thermal conductivities were higher than the out-of-plane thermal conductivities, and the thermal conductivities of both directions proportionally increased with the graphene loadings in the PIG composites. The temperature-dependent stresses of the composite films monotonically decreased with the graphene loadings. The experimentally obtained thermal characteristics of the polyimide-graphene composites were compared and discussed on the basis of the composite morphologies.